Analgesic effect of intrapocket anesthesia gel during scaling and root planing: A randomized crossover study - Yamamoto, Tatsuo; Kida, Sayuri; Sekino, Jin; Ichikawa, Yuka; Irie, Koichiro; Hanamura, Hiroyuki; Fukuda, Shuji; Miyake, Miyo; Kouno, Kanji; Ueda, Kana; Ishii, Rikako; Hosokawa, Miwa; et al. (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 2024)
In this study, a surface anesthetic gel injected into periodontal pockets (gel anesthesia) and infiltration anesthesia were compared to assess their analgesic effects and periodontal tissue improvements during scaling and root planing (SRP).Twenty-seven patients (16 males, aged 37-77 years) with four or more periodontal pockets (5-9 mm) were randomly divided into two groups. In the first session, group A received gel anesthesia on one tooth and infiltration anesthesia on another tooth, followed by infiltration and gel anesthesia in the second session, along with SRP. Group B received the reverse order of anesthesia described for Group A. After SRP, patients were asked to report the pain with a visual analogue scale and verbal rating scale, and preference of anesthesia and the reasons. The periodontal tissues were re-evaluated one month after the average SRP.No significant differences were observed in subject unit attributes or tooth unit clinical data between groups A and B. Although all pain indices were significantly higher for gel anesthesia than for infiltration anesthesia (p<0.01), 16 (59%) patients preferred gel anesthesia due to the lack of discomfort, such as pain during anesthetic needle insertion and postoperative numbness. Regardless of the type of anesthesia, periodontal tissue inflammation demonstrated significant improvement at re-evaluation (p<0.001). These results suggest that the injection of a surface anesthetic gel into the periodontal pockets before SRP is the preferred option for patients undergoing infiltration anesthesia.